RIJCMPH 2020
DOI: 10.37179/rijcmph.000009
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Regular Physical Exercise on the Advanced Glycated End Products

Abstract: Advanced Glycated End-products (AGEs) are heterogeneous glycated metabolites of protein, lipid, or nucleic acid. They are products of a chain of chemical reactions endogenously or diet and tobacco smoking exogenously. They exert signi􀏐icant pathological effects on many body tissues, leading to chronic disease complications such as diabetes, cardiovascular diseases, Alzheimer’s disease, etc. This narrative review shows that there are no agreed management options to reduce AGEs level. However, regular Physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…We have previously observed similar results in our cross-sectional study, where children with higher CRF demonstrated lower levels of sAGEs compared to those with lower CRF ( Köchli et al, 2020 ). These findings are consistent with a review in adults, which emphasized the beneficial effects of regular PA on AGEs levels ( Alyafei et al, 2020 ). Therefore, it is plausible that regular PA and improved CRF may have a protective effect against the endogenous accumulation of AGEs.…”
Section: Discussionsupporting
confidence: 92%
“…We have previously observed similar results in our cross-sectional study, where children with higher CRF demonstrated lower levels of sAGEs compared to those with lower CRF ( Köchli et al, 2020 ). These findings are consistent with a review in adults, which emphasized the beneficial effects of regular PA on AGEs levels ( Alyafei et al, 2020 ). Therefore, it is plausible that regular PA and improved CRF may have a protective effect against the endogenous accumulation of AGEs.…”
Section: Discussionsupporting
confidence: 92%
“…Some of the studied group also indicated that general practitioners were not expert in psychiatry; in other words, they are not specialized psychiatrists, thus constituting a hurdle of communication between them and the physicians. In relating NPMI to patient's barriers, our study reported significantly both doctor gender affecting consultation about psychological problems and that relation with the general practitioner is being not good enough to allow them to discuss their psychological problems [53][54][55].…”
Section: Factors Affecting Patients' Disclosure Of Their Psychologica...mentioning
confidence: 99%
“…A possible explanation for the cardiopulmonary effect of PE could be the followings, as shown in (Figure ( 1): [13][14][15], (Figure 1): The mechanism of physical exercise on improving the cardiopulmonary system. The drop in resting cardiac rate is properly secondary to the heart muscles' training on more blood needs, which ultimately cause a relative physiological rise in the left ventricular muscle mass.…”
Section: Physical Exercise Effect On Cardiopulmonary Systemmentioning
confidence: 99%